A comparison of platelet parameters in type -2 diabetics, pre-diabetics and normal subjects - Bindu Singh Gaur; Ishan Dubey; Amit Gupta (International Journal of Medical Research and Review, 2016)
Introduction: Diabetes Mellitus is a global pandemic disease. The increased platelet activity is emphasized to play a role in the development of vascular complications of the metabolic disorder. Mean platelet volume (MPV) is an indicator of average size and activity of platelets. This study is conducted to compare the platelet parameters in diabetics, pre-diabetics and normal subjects and to find correlation between glycemic control determinants (fasting plasma glucose) and platelet parameters (MPV, platelet count, platelet distribution width) in all the three groups and to correlate the duration of diabetes with MPV.Material and Methods: Total of 300 subjects (100 subjects in each group) were enrolled in the study. Sample for glucose estimation and platelet parameters were collected and estimation was carried out by the auto-analyzers. The statistical evaluation is done using SPSS version 22. Analysis of variance (ANOVA) and Pearson's correlation test are used to compare the variables and to see the correlation between the different variables respectively.Result: MPV a marker of platelet function and activation, is significantly higher in patients with type -2 diabetes mellitus than in control and pre-diabetic group with p- value <0.001 which is highly significant. FPG shows no correlation with platelet count and platelet distribution width. Also no correlation was seen between MPV and duration of diabetes.Conclusion: MPV can be used as a simple and cost effective tool to monitor the progression and control of diabetes and thereby preventing impending acute vascular events in health care centres.